3D printed cranioplasty moulds and a 3D optical scanner: A novel approach to reconstruction of challenging post-traumatic defects. Issue 1 (January 2023) - Wellham, Annabelle Margaret Lucy; Hurrell, Michael James Leslie; Collier, Ryan Christopher; Morrison, David Anthony; Ricciardo, Peter Virgil
Abstract: Objective: To describe and assess two cases of a delayed post-traumatic recontouring of the frontal bone using a novel technique. Materials and methods: Using rapid prototyping, patient specific sterilisable moulds were constructed from mirrored intact contralateral anatomy. The moulds were used intraoperatively to contour calcium phosphate cement at the bone defect. The accuracy of reconstruction was evaluated post operatively through comparisons of planned and actual reconstruction data from a three-dimensional optical scanner. Results: The contour of both defects was well restored clinically and there was no significant difference between the computer planned reconstructions and the actual reconstructions, with a mean difference of 0.4 cm 3 . Conclusion: Supraorbital rim disruption, commonly associated with fracture of the frontal bone, can be difficult to reconstruct aesthetically. This technique is a time-efficient and accurate way to reconstruct three-dimensional facial anatomy.